2013
DOI: 10.1177/0267659113513822
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol decreases total atrial conduction time in patients with peripheral artery disease

Abstract: Our results showed that 200 mg cilostazol treatment decreased TACT duration in patients with peripheral artery disease, which may also prevent the development and/or recurrence of atrial fibrillation (AF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These are PWD that is an electrocardiographic parameter and AEMD and ACT that are measured by TDI study (13)(14)(15)(16)(17) . In addition, in various contributing factors to develop AF such as obstructive sleep apnoea, diastolic dysfunction, dilated cardiomyopathy and hypertension the prolongation of AEMD during sinus rhythm has been reported (12,(18)(19)(20)(21) . Therefore, increase in AEMD is an electrophysiological marker that predisposes a patient to develop AF.…”
Section: Discussionmentioning
confidence: 99%
“…These are PWD that is an electrocardiographic parameter and AEMD and ACT that are measured by TDI study (13)(14)(15)(16)(17) . In addition, in various contributing factors to develop AF such as obstructive sleep apnoea, diastolic dysfunction, dilated cardiomyopathy and hypertension the prolongation of AEMD during sinus rhythm has been reported (12,(18)(19)(20)(21) . Therefore, increase in AEMD is an electrophysiological marker that predisposes a patient to develop AF.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that the evidence regarding cilostazol and tachyarrhythmia is still limited and unclear. Currently, as we know, there are fewer studies that directly have investigated the effect of cilostazol in AF In a recent study, Alizade et al (36) indicated that cilostazol could decrease total atrial conduction time duration in patients with peripheral artery disease, which may also prevent the development and/or recurrence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Cilostazol is used for the effective treatment of intermittent claudication, which is a chronic arterial occlusive disease in clinical practice. Alizade et al [18] showed that cilostazol decreased the duration of the total atrial conduction time in patients with peripheral artery disease, and cilostazol may also prevent the development and/or recurrence of AF. However, the potential mechanisms of cilostazol treatment remain unclear.…”
Section: Introductionmentioning
confidence: 99%